Synthesis , Characterization and computional study of Some New Aniline oxide derivatives - Turki, Afaq A. (University of Thi-Qar Journal, 2019)
The reaction of N-(4-(5-(furan-2-yl)-4,5-dihydro-1H-pyrazol-3-yl)phenyl) hydroxylamine (1) with aldehydes (2-6) in the presence of weak acid as a catalyst afforded the corresponding aniline oxide derivatives (7-11). The structures of these products were characterized by their elemental analysis (C.H.N.), 1H NMR